An analysis of crashes involving farm equipment as reported in the Kansas Department of Transportation database from the years 2015-2024 - Sultz, Madison (My University, 2026)
This study aims to analyze crash data involving farm equipment in Kansas from 2015-2024 to identify the common types of crashes and where they occur. By understanding these patterns, we can further investigate the underlying causes of these incidents. Kansas Department of Transportation crash reports were reviewed for crashes involving farm equipment in Kansas from 2015 to 2024. Key data points included the date, time, type of incident, weather, and lighting conditions. For each report, the incident narrative, age of drivers, and types of vehicles were also used. These factors were analyzed to gain insights into the nature of each incident. From 2015 to 2024, 1,032 reported crashes involving farm equipment occurred. Many of these crashes happened in the afternoon in daylight, on blacktop roadways, with no adverse conditions. The incidents that occurred most frequently were rear-end collisions (n = 200, 19.4%), left-hand turns (n = 176, 17%), collisions with fixed objects (n = 149, 14.4%), and sideswipes (n = 122, 11.9%). Of the 732 crashes that occurred between farm equipment and passenger vehicles, 507 (69%) resulted in more damage, injury, or fatality in the passenger vehicle than the farm equipment. Further research is needed to understand the contributing factors of crashes involving farm equipment. Limitations of this analysis are the underreporting of crashes, particularly those occurring on private property or those with minimal damage and reporting officers with limited knowledge of farm equipment terms. A continuation of this study will focus on high-crash areas to develop targeted mitigation strategies.
Keywords: Farm equipment; Crashes; Traffic; Tractor; Roadway; Safety